PELAYANAN E-SPT OLEH PARA RELAWAN PAJAK DI KPP DJP WILAYAH SUMUT 1 MEDAN - Melanthon Rumapea; Arthur Simanjuntak; Duma M. Elisabeth; Mitha C. Ginting; Lamria Sagala; Sahala Purba; Septony B. Siahaan; Dompak Pasaribu; Rike Y. Panjaitan; Wesly A. Simanjuntak; Rimky M. P. Simanjuntak; Gracesiela Y. Simanjuntak (Universitas Methodist Indonesia, 2021)
This community service activity is one of the manifestations of the Tri Dharma Perguruan Tinggi, which is to provide benefits to the community in this case to taxpayers who are domiciled at the Tax Service Office (KPP) in the working area of ​​the Directorate General of Taxes (DJP) of North Sumatra 1. Several KPPs that were appointed partners were KPPs of Medan Timur, Medan Petisah, Binjai and Lubuk Pakam. These activities include serving taxpayers, discussing, helping to calculate, and determining the amount of income tax deposits that must be fulfilled by taxpayers along with filling and reporting their annual SPT online (e-SPT). For the Indonesian Methodist University, especially the Faculty of Economics, this activity is a role to support the Government, especially in the inclusion of tax awareness which is being activated and programmed by the Directorate General of Taxes as well as to better foster relationships with the surrounding community. This activity begins with a meeting to explore the needs of partners, in this case, the DGT/KPP. Then the Tax Volunteer recruitment process is carried out in the form of written tests and interviews. Next, we compiled soft skills material for Tax Volunteers, namely FE UMI students who had been trained as volunteers, and coordinated the timing of this activity.